A kind of amphiphilic quasi-solid polymer electrolyte and preparation method thereof and lithium ion battery
By using the preparation method of amphiphilic quasi-solid polymer electrolyte in lithium-ion batteries, the safety and cycle stability problems of traditional lithium-ion batteries when using metal lithium negative electrodes are solved, and a lithium-ion battery with high safety and high cycle stability is achieved.
Patent Information
- Application Number
- CN202410931033.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-12
- Publication Date
- 2025-04-29
- Estimated Expiration
- 2044-07-12
AI Technical Summary
When using metal lithium negative electrodes in traditional lithium batteries, side reactions are prone to occur, resulting in short circuits and thermal runaway from the battery, affecting safety performance and cycle stability.
By using the preparation method of an amphiphilic quasi-solid polymer electrolyte, a lithium salt, isocyanoacrylate, fluorinated acrylate, a crosslinking agent and a plasticizer, then mixing with a thermal initiator and reacting heat to form an amphiphilic quasi-solid polymer electrolyte with thermal shutdown and flame retardant properties.
It improves the safety of use and cycle stability of lithium-ion batteries, achieves high ionic conductivity and excellent flame retardant performance, and enhances the thermal shutdown function of the battery.
Smart Images

Figure CN118852519B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of lithium ion batteries, and in particular to an amphiphilic quasi-solid polymer electrolyte and a preparation method thereof, and a lithium ion battery. Background Art
[0002] With the rapid development of the new energy vehicle industry, producing power batteries with high energy density and high safety has become an unremitting goal in this field. x Co y Mn 1-x-y O2, NCM, x>0.5) can effectively increase the battery energy density to 450Wh / kg, so the metal lithium electrode has become the focus of attention. Currently, commercial lithium-ion batteries generally use an organic electrolyte (LE) system. When lithium metal is selected as the negative electrode, the lithium negative electrode is very likely to react with the organic electrolyte during the charge and discharge cycle to form dendrites, pierce the diaphragm to cause a short circuit in the battery, and cause thermal runaway, thereby causing a series of safety problems. Therefore, the metal lithium negative electrode has not been used in traditional lithium-ion batteries, resulting in limited room for improving the battery's energy density.
[0003] Solid polymer electrolytes (SPEs) stand out for their strong thermal stability and non-volatility. However, their practical application is hampered by poor ionic conductivity and poor interfacial properties with electrodes. To solve this problem, an intermediate electrolyte state, namely quasi-solid polymer electrolyte (QSPE), was obtained by gelling liquid solvents to form a solid polymer matrix. QSPE has the combined advantages of SPE and LE, including high ionic conductivity and good interfacial stability. Since the precursor electrolyte of QSPE has a viscosity similar to that of traditional liquid electrolytes, it can easily penetrate into the entire area of the battery. The subsequent polymerization will form an integrated structure of a three-dimensional network for the entire battery, ensuring close contact between the solid electrolyte and the electroactive particles, making the interfacial resistance of the battery significantly lower than that of the battery using prefabricated polymer films as electrolytes.
[0004] However, the solvents or plasticizers used in the preparation of QSPE are usually hydrocarbon-based flammable liquids, which can reduce the safety performance of the battery. In the current solution, on the one hand, flame retardant additives such as organic phosphates, including trimethyl phosphate, triethyl phosphate or diphenyl octyl phosphate, etc. can be added, but phosphate flame retardant additives can reduce the conductivity of the electrolyte and affect the electrochemical performance of the battery; on the other hand, non-flammable solvents such as fluorinated solvents, phosphate solvents or nitrile solvents can be used, however, the interface between the solid electrolyte formed by the non-flammable solvent and the lithium metal negative electrode still has the problem of poor stability. The solid electrolyte interface cannot passivate the lithium metal negative electrode, resulting in continuous side reactions between the non-flammable solvent and the lithium metal negative electrode, which ultimately reduces the cycle stability of the lithium metal battery. Summary of the invention
[0005] The purpose of the present invention is to provide an amphiphilic quasi-solid polymer electrolyte and a preparation method thereof and a lithium ion battery. The lithium ion battery prepared by the amphiphilic quasi-solid polymer electrolyte prepared by the preparation method provided by the present invention has excellent use safety and can make the lithium ion battery have high cycle stability.
[0006] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0007] The present invention provides a method for preparing an amphiphilic quasi-solid polymer electrolyte, comprising the following steps:
[0008] (1) mixing lithium salt, isocyanoacrylate, fluorinated acrylate, crosslinking agent and plasticizer to obtain a raw material premix solution;
[0009] (2) performing a second mixing of the raw material premix obtained in step (1) and a thermal initiator to obtain a precursor solution;
[0010] (3) subjecting the precursor solution obtained in step (2) to a thermal polymerization reaction to obtain an amphiphilic quasi-solid polymer electrolyte.
[0011] Preferably, in step (1), the molar ratio of isocyanoacrylate, fluorinated acrylate and crosslinking agent is (0.1-1):1:(0.05-0.5);
[0012] The ratio of the total amount of the isocyanoacrylate, the fluorinated acrylate and the crosslinking agent to the amount of the plasticizer is 1:(0.5-0.8).
[0013] Preferably, the concentration of lithium salt in the raw material premix in step (1) is 0.7 to 1 mol / L.
[0014] Preferably, the isocyanoacrylate in step (1) includes one or more of isocyanoethyl methacrylate, 2-isocyanoethyl acrylate and 1,1-bis(acryloyloxymethyl)ethyl isocyanate.
[0015] Preferably, the fluorinated acrylate in step (1) comprises one or more of perfluoroalkylethyl methacrylate, 2-(perfluorooctyl)ethyl methacrylate, hexafluorobutyl methacrylate and 2,2,3,4,4,4-hexafluorobutyl acrylate.
[0016] Preferably, the crosslinking agent in step (1) comprises ethoxylated trimethylolpropane triacrylate and / or hydroxymethyl ethoxylated trimethylolpropane triacrylate.
[0017] Preferably, the mass of the thermal initiator in step (2) is 0.1 to 1% of the mass of the raw material premix.
[0018] Preferably, the temperature of the thermal polymerization reaction in step (3) is 60 to 80° C., and the time of the thermal polymerization reaction is 1 to 2 hours.
[0019] The present invention also provides an amphiphilic quasi-solid polymer electrolyte prepared by the preparation method described in the above technical solution.
[0020] The present invention also provides a lithium ion battery, wherein the electrolyte in the lithium ion battery is the amphiphilic quasi-solid polymer electrolyte described in the above technical solution.
[0021] The present invention provides a method for preparing an amphiphilic quasi-solid polymer electrolyte, comprising the following steps: (1) first mixing a lithium salt, an isocyanoacrylate, a fluorinated acrylate, a crosslinking agent and a plasticizer to obtain a raw material premix solution; (2) second mixing the raw material premix solution obtained in step (1) with a thermal initiator to obtain a precursor solution; and (3) subjecting the precursor solution obtained in step (2) to an in-situ thermal polymerization reaction in a lithium ion battery to obtain an amphiphilic quasi-solid polymer electrolyte. The present invention uses a thermal initiator to initiate an in-situ thermal polymerization reaction of fluorinated acrylate, isocyanoacrylate and a crosslinking agent, and grafts isocyanoacrylate with an N=C=O group and a fluorinated acrylate with a CF3 group onto the crosslinking agent. Under the combined action of the flame-retardant CF3 group and the thermal shutdown N=C=O group, the obtained amphiphilic quasi-solid polymer electrolyte can have thermal shutdown and flame retardant properties without the need to add additional flame retardants or select non-flammable plasticizers, thereby improving the safety of batteries prepared from the quasi-solid polymer electrolyte; at the same time, the introduction of the N=C=O group can construct an electrode-electrolyte interface in one step, thereby improving the cycle stability of lithium-ion batteries. The results of the embodiment show that the amphiphilic quasi-solid polymer electrolyte obtained by the preparation method provided by the present invention has an ionic conductivity of 1.3×10-4 S cm -1 , with high ionic conductivity; after the amphiphilic quasi-solid polymer electrolyte membrane is ignited, no obvious blackening and coking phenomenon occurs on the surface, and the self-extinguishing time (SET) value is 0s; the total impedance of the lithium ion battery prepared by using the amphiphilic quasi-solid polymer electrolyte of the present invention increases from 345.35Ω to 2584.89Ω before and after heating at 175°C for 10min, and has excellent safety in use; and the lithium ion battery is cycled 220 times at 1C, and the capacity retention rate can reach 92.7%, with high cycle stability. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 The thermal polymerization process diagram in Example 1 of the present invention; wherein a is the precursor solution, and b is the amphiphilic quasi-solid polymer electrolyte after thermal polymerization;
[0023] Figure 2 is an assembly flow chart of the lithium-ion battery of the present invention;
[0024] Figure 3 This is a macroscopic photograph of the amphiphilic quasi-solid polymer electrolyte prepared in Example 1 of the present invention;
[0025] Figure 4 This is a SEM image of the amphiphilic quasi-solid polymer electrolyte and the polyethylene separator prepared in Example 1 of the present invention; wherein a is the amphiphilic quasi-solid polymer electrolyte membrane, and b is the polyethylene separator;
[0026] Figure 5 The impedance spectrum of the amphiphilic quasi-solid polymer electrolyte prepared in Example 1 of the present invention;
[0027] Figure 6 The linear sweep voltammetry curve of the amphiphilic quasi-solid polymer electrolyte prepared in Example 1 of the present invention;
[0028] Figure 7 This is a flame retardant performance diagram of the amphiphilic quasi-solid polymer electrolyte membrane and tetraethylene glycol dimethyl ether plasticizer prepared in Example 1 of the present invention; wherein a is tetraethylene glycol dimethyl ether plasticizer, and b is the amphiphilic quasi-solid polymer electrolyte membrane;
[0029] Figure 8 The SEM images of the amphiphilic quasi-solid polymer electrolyte prepared in Example 1 of the present invention before heating and after heating at 175°C for 10 minutes; wherein a is before heating with a scale of 10 μm, b is before heating with a scale of 5 μm, c is after heating for 10 minutes with a scale of 10 μm, and d is after heating for 10 minutes with a scale of 5 μm;
[0030] Fig. 9The impedance spectra of the lithium-ion battery in Application Example 1 of the present invention at room temperature (RT) and after being heated at 175°C for 10 minutes (175°C);
[0031] Fig.10 This is the cycle performance curve of the lithium-ion battery in Application Example 1 of the present invention at a 1C rate. DETAILED DESCRIPTION
[0032] The present invention provides a method for preparing an amphiphilic quasi-solid polymer electrolyte, comprising the following steps:
[0033] (1) mixing lithium salt, isocyanoacrylate, fluorinated acrylate, crosslinking agent and plasticizer to obtain a raw material premix solution;
[0034] (2) performing a second mixing of the raw material premix obtained in step (1) and a thermal initiator to obtain a precursor solution;
[0035] (3) subjecting the precursor solution obtained in step (2) to a thermal polymerization reaction to obtain an amphiphilic quasi-solid polymer electrolyte.
[0036] The present invention first mixes lithium salt, isocyanoacrylate, fluorinated acrylate, a crosslinking agent and a plasticizer to obtain a raw material premix liquid.
[0037] In the present invention, the isocyanoacrylate preferably includes one or more of isocyanoethyl methacrylate (Formula I-1), 2-isocyanoethyl acrylate (Formula I-2) and 1,1-bis(acryloyloxymethyl)ethyl isocyanate (Formula I-3). In the present invention, the N=C=O group provided by the isocyanoacrylate can make the electrolyte have thermal shutdown properties. By limiting the type of isocyanoacrylate to the above range, it can be ensured that the quasi-solid polymer electrolyte has good thermal shutdown properties, further improving the safety of the battery and ensuring the cycle stability of the battery.
[0038]
[0039] In the present invention, the fluorinated acrylate preferably includes one or more of perfluoroalkylethyl methacrylate (Formula II-1), 2-(perfluorooctyl)ethyl methacrylate (Formula II-2), hexafluorobutyl methacrylate (Formula II-3) and 2,2,3,4,4,4-hexafluorobutyl acrylate (Formula II-4). In the present invention, the CF3 group provided by the fluorinated acrylate has flame retardant properties. By limiting the type of fluorinated acrylate to the above range, it can be ensured that the quasi-solid polymer electrolyte has good flame retardant properties, further improving the safety of the battery.
[0040]
[0041] In the present invention, the crosslinking agent preferably includes ethoxylated trimethylolpropane triacrylate (Formula III-1) and / or hydroxymethyl ethoxylated trimethylolpropane triacrylate (Formula III-2). In the present invention, the crosslinking agent can crosslink isocyanoacrylate and fluorinated acrylate, and by limiting the type of the crosslinking agent to the above range, the smooth progress of the crosslinking reaction can be ensured to ensure the electrochemical performance of the lithium ion battery.
[0042]
[0043] In the present invention, the molar ratio of the isocyanoacrylate, the fluorinated acrylate and the crosslinking agent is preferably (0.1-1):1:(0.05-0.5), more preferably (0.2-0.5):1:(0.05-0.2), and further preferably (0.3-0.4):1:0.1. The present invention limits the molar ratio of the isocyanoacrylate, the fluorinated acrylate and the crosslinking agent to the above range, so as to control the grafting amount of the isocyanoacrylate and the fluorinated acrylate on the crosslinking agent, and make the flame retardant CF3 group and the thermal shutdown N=C=O group work together, further improving the safety of the battery prepared by the quasi-solid polymer electrolyte.
[0044] In the present invention, the plasticizer is preferably one or more of ethylene glycol dimethyl ether, triethylene glycol dimethyl ether and tetraethylene glycol dimethyl ether, and more preferably tetraethylene glycol dimethyl ether. In the present invention, the plasticizer can improve the ionic conductivity of the amphiphilic quasi-solid polymer electrolyte and reduce the interface impedance. By limiting the type of the plasticizer to the above range, the cycle stability of the battery can be further improved.
[0045] In the present invention, the ratio of the total amount of the isocyanoacrylate, the fluorinated acrylate and the crosslinking agent to the amount of the plasticizer is preferably 1: (0.5-0.8), more preferably 1: (0.6-0.7), and further preferably 1: 0.7. The present invention limits the ratio of the total amount of the isocyanoacrylate, the fluorinated acrylate and the crosslinking agent to the amount of the plasticizer to the above range, and the quasi-solid polymer electrolyte can have good flame retardant properties without using a non-flammable plasticizer; at the same time, the ionic conductivity of the amphiphilic quasi-solid polymer electrolyte can be further improved, the interface impedance can be reduced, and thus the cycle stability of the battery can be improved.
[0046] In the present invention, the lithium salt preferably includes one or more of lithium hexafluorophosphate, lithium perchlorate, lithium bistrifluoromethanesulfonyl imide, lithium bisfluorosulfonyl imide, lithium dioxalate borate and lithium difluorooxalate borate, and more preferably a mixture of lithium bistrifluoromethanesulfonyl imide and lithium difluorooxalate borate; the mass ratio of lithium bistrifluoromethanesulfonyl imide and lithium difluorooxalate borate in the mixture of lithium bistrifluoromethanesulfonyl imide and lithium difluorooxalate borate is preferably 10:1. The present invention limits the types of lithium salts to the above range, which can further improve the conductivity of the amphiphilic quasi-solid polymer electrolyte, thereby improving the performance of the lithium ion battery.
[0047] In the present invention, the concentration of lithium salt in the raw material premix is preferably 0.7-1 mol / L, more preferably 0.7-0.8 mol / L. The present invention limits the type and concentration of lithium salt to the above range to further improve the electrochemical performance of the battery prepared by the electrolyte.
[0048] In the present invention, the first mixing is preferably carried out under stirring conditions; the stirring speed is preferably 100 to 300 r / min; the temperature of the first mixing is preferably room temperature; and the time of the first mixing is preferably 5 to 12 hours. The present invention limits the speed, temperature and time of the first mixing to the above ranges so that the reactants can be mixed evenly, which is beneficial to the free radical reaction in the subsequent heating process.
[0049] After obtaining the raw material premix, the present invention performs a second mixing of the raw material premix with a thermal initiator to obtain a precursor solution.
[0050] In the present invention, the thermal initiator preferably includes azobisisobutyronitrile and / or azobisisoheptanenitrile, more preferably azobisisobutyronitrile; the mass of the thermal initiator is preferably 0.1-1% of the mass of the raw material premix, more preferably 0.3-0.8%, and further preferably 0.5%. In the present invention, the thermal initiator initiates the polymerization reaction, and the thermal polymerization reaction can be smoothly carried out by limiting the type and content of the thermal initiator to the above range.
[0051] In the present invention, the second mixing is preferably carried out under stirring conditions; the stirring speed is preferably 100 to 300 r / min; the temperature of the second mixing is preferably room temperature; and the time of the second mixing is preferably 1 to 2 hours. The present invention limits the speed, temperature and time of the second mixing to the above ranges, so that the reaction materials can be fully mixed and uniform, and avoid the thermal initiator and the monomer reagent from spontaneously undergoing free radical polymerization.
[0052] After the precursor solution is obtained, the present invention performs a thermal polymerization reaction on the precursor solution to obtain an amphiphilic quasi-solid polymer electrolyte.
[0053] In the present invention, the temperature of the thermal polymerization reaction is preferably 60-80°C, more preferably 70°C; the time of the thermal polymerization reaction is preferably 1-2h, more preferably 1-1.5h; the thermal polymerization reaction is preferably carried out in a vacuum oven. In the present invention, during the thermal polymerization reaction, the N=C=O group on the isocyanoacrylate and the CF3 group on the fluorinated acrylate are grafted onto the crosslinking agent to form a crosslinked polymer. By limiting the temperature and time of the thermal polymerization reaction to the above range, the thermal polymerization reaction can be fully carried out, thereby improving the performance of the lithium-ion battery prepared by the amphiphilic quasi-solid polymer electrolyte.
[0054] In the present invention, the precursor solution is preferably spread in a container to carry out a thermal polymerization reaction to obtain an amphiphilic quasi-solid polymer electrolyte membrane.
[0055] In the present invention, when the amphiphilic quasi-solid polymer electrolyte is applied to a lithium-ion battery, the present invention preferably injects the precursor solution into the electrolyte position of the lithium-ion battery for in-situ thermal polymerization reaction to obtain the amphiphilic quasi-solid polymer electrolyte. The present invention has no special limitation on the operation of injecting the precursor solution into the lithium-ion battery, and the injection technical solution well known to those skilled in the art can be used.
[0056] The present invention utilizes fluorinated acrylate, isocyanoacrylate, a crosslinking agent and a thermal initiator to carry out an in-situ thermal polymerization reaction, and grafts isocyanoacrylate with an N=C=O group and a fluorinated acrylate with a CF3 group onto the crosslinking agent. Under the combined action of the flame-retardant CF3 group and the thermal shutdown N=C=O group, the amphiphilic quasi-solid polymer electrolyte has thermal shutdown and flame-retardant properties, thereby improving the safety of a battery prepared from the quasi-solid polymer electrolyte. At the same time, the introduction of the N=C=O group can construct an electrode-electrolyte interface in one step, thereby improving the cycle stability of the lithium-ion battery. By adding a plasticizer, the ionic conductivity of the amphiphilic quasi-solid polymer electrolyte is improved, the interface impedance is reduced, and the cycle stability of the battery is further improved.
[0057] The present invention also provides an amphiphilic quasi-solid polymer electrolyte prepared by the preparation method described in the above technical solution.
[0058] The present invention also provides a lithium ion battery, wherein the electrolyte in the lithium ion battery is the amphiphilic quasi-solid polymer electrolyte described in the above technical solution.
[0059] In the present invention, the lithium-ion battery preferably comprises a positive electrode, a negative electrode, a barrier medium and an electrolyte; the electrolyte is an amphiphilic quasi-solid polymer electrolyte. In the present invention, the positive electrode is preferably LiNi x Co y Mn 1-x-yO2 (x>0.5), more preferably LiNi 0.6 Co 0.2 Mn 0.2 O2; the negative electrode is preferably metallic lithium; the barrier medium is preferably a diaphragm; the diaphragm preferably includes one or more of polyethylene, polypropylene, cellulose and glass fiber, more preferably polyethylene or polypropylene; the thickness of the diaphragm is preferably 10 to 100 μm, more preferably 10 to 50 μm.
[0060] In the present invention, the specific operation of assembling the lithium-ion battery is preferably: after assembling the positive electrode, the barrier medium and the negative electrode in sequence, injecting the precursor solution, so that the barrier medium is completely infiltrated and then thermally polymerized and reacted to obtain a lithium-ion battery. The present invention does not specifically limit the volume of the injected precursor solution, and it can be conventionally selected according to the volume of the lithium-ion battery. In an embodiment of the present invention, the volume of the injected precursor solution is preferably 20 to 50 μL, more preferably 30 μL.
[0061] In the present invention, the lithium-ion battery is preferably assembled in a glove box filled with argon; the contents of H2O and O2 in the glove box filled with argon are preferably independently ≤0.1 ppm.
[0062] The technical solutions in the present invention will be described clearly and completely below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0063] Example 1
[0064] A method for preparing an amphiphilic quasi-solid polymer electrolyte comprises the following steps:
[0065] (1) Lithium bis(trifluoromethanesulfonyl)imide, isocyanoethyl methacrylate (Formula I-1), 2,2,3,4,4,4-hexafluorobutyl methacrylate (Formula II-3), ethoxylated trimethylolpropane triacrylate (Formula III-1) and tetraethylene glycol dimethyl ether are stirred at a speed of 300 r / min for 12 hours to obtain a raw material premix; the isocyanoethyl methacrylate (Formula I-1), 2,2,3,4,4,4-hexafluorobutyl methacrylate (Formula II-3) and ethoxylated trimethylolpropane triacrylate (Formula III-1) are stirred at a speed of 300 r / min for 12 hours to obtain a raw material premix; The molar ratio of hydroxymethylpropane triacrylate (Formula III-1) is 0.33:1:0.1; the molar ratio of the total molar ratio of isocyanoethyl methacrylate (Formula I-1), 2,2,3,4,4,4-hexafluorobutyl methacrylate (II-3) and ethoxylated trimethylolpropane triacrylate (Formula III-1) to the molar ratio of tetraethylene glycol dimethyl ether is 1:0.7; the molar concentration of the lithium bistrifluoromethanesulfonyl imide in the raw material premix is 0.8 mol / L;
[0066] (2) stirring the raw material premix obtained in step (1) and azobisisobutyronitrile at a speed of 300 r / m for 1 h to obtain a precursor solution; the mass percentage of the azobisisobutyronitrile is 0.5% of the raw material premix;
[0067] (3) heating the precursor solution obtained in the step (2) in a vacuum oven at 70° C. for 1 h, initiating a thermal polymerization reaction with a thermal initiator, and obtaining an amphiphilic quasi-solid-state polymer electrolyte (amphiphilic quasi-solid-state polymer electrolyte membrane); the thickness of the amphiphilic quasi-solid-state polymer electrolyte (amphiphilic quasi-solid-state polymer electrolyte membrane) is 20 μm.
[0068] Example 2
[0069] The only difference between Example 2 and Example 1 is that 2,2,3,4,4,4-hexafluorobutyl methacrylate (Formula II-3) is replaced by perfluoroalkylethyl methacrylate (Formula II-1), and the rest is the same as Example 1.
[0070] Example 3
[0071] The only difference between Example 3 and Example 1 is that isocyanoethyl methacrylate (Formula I-1) is replaced by 2-isocyanoethyl acrylate (Formula I-2), and the rest is the same as Example 1.
[0072] Example 4
[0073] The difference between Example 4 and Example 1 is that ethoxylated trimethylolpropane triacrylate (Formula III-1) is replaced by ethoxylated trimethylolpropane triacrylate (Formula III-2), and the rest is the same as Example 1.
[0074] Application Examples 1 to 4
[0075] A lithium-ion battery:
[0076] The battery was assembled in an argon-filled glove box (H2O and O2 contents were both ≤ 0.1 ppm) with LiNi x Co y Mn 1-x- y O2 (x>0.5) is used as the positive electrode, metallic lithium is used as the negative electrode, and a 17μm thick polyethylene diaphragm is used as the barrier medium. 35μL of the precursor solution obtained in Examples 1 to 4 is injected to completely soak the barrier medium, and then it is placed in a 70℃ vacuum oven and heated for 1h for thermal polymerization to obtain a lithium-ion battery.
[0077] The microscopic morphology of the amphiphilic quasi-solid polymer electrolyte (amphiphilic quasi-solid polymer electrolyte membrane) was observed using a scanning electron microscope.
[0078] The impedance of the amphiphilic quasi-solid polymer electrolyte (amphiphilic quasi-solid polymer electrolyte membrane) was tested by electrochemical impedance spectroscopy (Princeton P4000 electrochemical workstation) at room temperature and constant pressure EIS, with the test frequency range of 1 MHz to 1 Hz;
[0079] The electrochemical window of the amphiphilic quasi-solid polymer electrolyte (amphiphilic quasi-solid polymer electrolyte membrane) was tested by linear sweep voltammetry, with the test voltage range from OCV to 6V;
[0080] The charge and discharge process and cycle stability of lithium-ion batteries were tested at room temperature and a voltage of 2.8 to 4.3 V using a LAND CT2001A test system.
[0081] The thermal polymerization process in Example 1 is shown in FIG. Figure 1 As shown, a is the precursor solution, b is the amphiphilic quasi-solid polymer electrolyte after polymerization, Figure 1 It can be seen that the thermal polymerization and reaction are complete and there is no flowing liquid.
[0082] The assembly flow chart of lithium-ion batteries is as follows: Figure 2 As shown, from Figure 2 It can be seen that the precursor solution is dropped onto the barrier medium, and after the barrier medium is soaked, it is heated at 70°C to obtain a lithium-ion battery.
[0083] The macroscopic photograph of the amphiphilic quasi-solid polymer electrolyte (amphiphilic quasi-solid polymer electrolyte membrane) prepared in Example 1 is shown in FIG. Figure 3 As shown, from Figure 3 It can be seen that it is transparent and bendable; the SEM image of the amphiphilic quasi-solid polymer electrolyte (amphiphilic quasi-solid polymer electrolyte membrane) prepared in Example 1 is as follows Figure 4 As shown, from Figure 4It can be seen that there is a uniform 3D wrinkled structure on the surface of the amphiphilic quasi-solid polymer electrolyte, which is conducive to the transmission of lithium ions.
[0084] The impedance spectrum of the amphiphilic quasi-solid polymer electrolyte (amphiphilic quasi-solid polymer electrolyte membrane) prepared in Example 1 is shown in FIG. Figure 5 As shown by Figure 5 The resistance R of the electrolyte is known, where R is 7.19Ω. According to Formula 1, the room temperature ionic conductivity of the quasi-solid polymer electrolyte provided by the present invention is 1.3×10 -4 S / cm, where σ is the ionic conductivity (S / cm), l is the thickness of the solid polymer electrolyte membrane (cm), R is the resistance of the electrolyte (Ω), and s is the effective area of the solid polymer electrolyte (cm 2 ).
[0085]
[0086] The linear sweep voltammetric curve of the amphiphilic quasi-solid polymer electrolyte (amphiphilic quasi-solid polymer electrolyte membrane) prepared in Example 1 is as follows: Figure 6 As shown, from Figure 6 It can be seen that the oxidation potential of the electrolyte membrane is greater than 5V, which is attributed to the introduction of high-voltage resistant functional groups CF3 and N=C=O. Even when tetraethylene glycol dimethyl ether plasticizer with an oxidation potential of 4V is added, high oxidation stability can still be maintained.
[0087] The flame retardant performance of the amphiphilic quasi-solid polymer electrolyte (amphiphilic quasi-solid polymer electrolyte membrane) and tetraethylene glycol dimethyl ether plasticizer prepared in Example 1 is shown in FIG. Figure 7 As shown, wherein a is a tetraethylene glycol dimethyl ether plasticizer, b is an amphiphilic quasi-solid polymer electrolyte membrane, Figure 7 It can be seen that the initial is the initial state of the amphiphilic quasi-solid polymer electrolyte membrane and tetraethylene glycol dimethyl ether plasticizer, the contact is the state of the amphiphilic quasi-solid polymer electrolyte membrane and tetraethylene glycol dimethyl ether plasticizer about to contact the open flame, 0s is the state of the amphiphilic quasi-solid polymer electrolyte membrane and tetraethylene glycol dimethyl ether plasticizer after contacting the open flame 0s, 3s is the state of the amphiphilic quasi-solid polymer electrolyte membrane and tetraethylene glycol dimethyl ether plasticizer after contacting the open flame 3s. By comparison, it is found that after the tetraethylene glycol dimethyl ether plasticizer contacts the open flame, it is found that it burns violently and presents a bright flame; after the amphiphilic quasi-solid polymer electrolyte membrane contacts the open flame, its surface does not undergo obvious blackening and charring, and the self-extinguishing time (SET) value is 0s, which has excellent flame retardant properties. This is due to the gas phase free radical scavenging effect of the CF3 functional group, which produces F free radicals at high temperatures. The F free radicals will combine with H free radicals to undergo elimination reactions, thereby inhibiting combustion and eliminating the inherent flammability of ether-based electrolytes.
[0088] The SEM images of the amphiphilic quasi-solid polymer electrolyte (amphiphilic quasi-solid polymer electrolyte membrane) prepared in Example 1 before and after heating at 175°C for 10 min are shown in FIG. Figure 8 As shown, a is the scale of 10 μm before heating, b is the scale of 5 μm before heating, c is the scale of 10 μm after heating for 10 min, and d is the scale of 5 μm after heating for 10 min. Figure 8 It can be seen that the 3D wrinkled structure of the electrolyte increases significantly after heating, that is, the cross-linking density increases, proving that it has a certain thermal shutdown function.
[0089] The impedance spectra of the lithium-ion battery of Application Example 1 at room temperature (RT) and after heating at 175°C for 10 minutes (175°C) are as follows: Fig. 9 As shown, from Fig. 9 It can be seen that after heating at 175℃ for 10min, the total impedance (bulk impedance, phase impedance and charge transfer impedance) of the button battery increased from 345.35Ω to 2584.89Ω, indicating that its ion transport kinetics at high temperature are slow and it has a certain thermal shutdown function.
[0090] The cycle performance curve of the lithium-ion battery in Application Example 1 at 1C rate is as follows: Fig.10 ,from Fig.10 It can be seen that after 220 cycles at a rate of 1C, the discharge capacity of the lithium-ion battery after the first cycle is 130 mAh / g, and the discharge capacity after 220 cycles is 120.5 mAh / g, and its capacity retention rate is 92.7%, indicating that the lithium-ion battery made of amphiphilic quasi-solid polymer electrolyte as the electrolyte has good cycle stability.
[0091] The room temperature ionic conductivity test data of the amphiphilic quasi-solid polymer electrolytes in Examples 1 to 4 are shown in Table 1.
[0092] Table 1 Room temperature ionic conductivity test data of the amphiphilic quasi-solid polymer electrolyte in Examples 1 to 4
[0093] Example Room temperature conductivity Example 1 <![CDATA[1.3×10 -4 S / cm]]> Example 2 <![CDATA[1.0×10 -4 S / cm]]> Example 3 <![CDATA[1.6×10 -4 S / cm]]> Example 4 <![CDATA[1.2×10 -4 S / cm]]>
[0094] The first cycle discharge specific capacity and capacity retention rate data after 220 cycles at 1C of the lithium-ion batteries in Application Examples 1 to 4 are shown in Table 2.
[0095] Table 2 The first cycle discharge capacity of lithium-ion batteries in application examples 1 to 4 and the capacity retention rate after 220 cycles at 1C
[0096]
[0097]
[0098] The amphiphilic quasi-solid polymer electrolyte prepared by the preparation method provided by the present invention has an ionic conductivity of 1.3×10 -4 S cm -1 , with high ionic conductivity; after the amphiphilic quasi-solid polymer electrolyte membrane was ignited, no obvious blackening and carbonization occurred on the surface, and the self-extinguishing time (SET) value was 0s. The total impedance of the lithium-ion battery prepared with the amphiphilic quasi-solid polymer electrolyte increased from 345.35Ω to 2584.89Ω before and after heating at 175°C for 10min, and it has excellent safety in use; the lithium-ion battery assembled with the amphiphilic quasi-solid polymer electrolyte was cycled 220 times at 1C, and the capacity retention rate could reach 92.7%, with high cycle stability.
[0099] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing an amphiphilic quasi-solid polymer electrolyte, comprising the following steps: (1) mixing lithium salt, isocyanoacrylate, fluorinated acrylate, crosslinking agent and plasticizer to obtain a raw material premix solution; (2) performing a second mixing of the raw material premix obtained in step (1) and a thermal initiator to obtain a precursor solution; (3) subjecting the precursor solution obtained in step (2) to a thermal polymerization reaction to obtain an amphiphilic quasi-solid polymer electrolyte; In the step (1), the molar ratio of isocyanoacrylate, fluorinated acrylate and crosslinking agent is (0.1-1):1:(0.05-0.5); the molar ratio of the total molar ratio of isocyanoacrylate, fluorinated acrylate and crosslinking agent to the molar ratio of plasticizer is 1: (0.5~0.8); The concentration of lithium salt in the raw material premix in step (1) is 0.7 to 1 mol / L.
2. The preparation method according to claim 1, characterized in that: The isocyanoacrylate in step (1) includes one or more of isocyanoethyl methacrylate, 2-isocyanoethyl acrylate and 1,1-bis(acryloyloxymethyl)ethyl isocyanate.
3. The preparation method according to claim 1, characterized in that: The fluorinated acrylate in step (1) includes one or more of perfluoroalkylethyl methacrylate, 2-(perfluorooctyl)ethyl methacrylate, hexafluorobutyl methacrylate and 2,2,3,4,4,4-hexafluorobutyl acrylate.
4. The preparation method according to claim 1, characterized in that: The crosslinking agent in step (1) includes ethoxylated trimethylolpropane triacrylate and / or hydroxymethyl ethoxylated trimethylolpropane triacrylate.
5. The preparation method according to claim 1, characterized in that: The mass of the thermal initiator in step (2) is 0.1-1% of the mass of the raw material premix.
6. The preparation method according to claim 1, characterized in that: The temperature of the thermal polymerization reaction in step (3) is 60 to 80° C., and the time of the thermal polymerization reaction is 1 to 2 hours.
7. An amphiphilic quasi-solid polymer electrolyte prepared by the preparation method according to any one of claims 1 to 6.
8. A lithium ion battery, characterized in that: The electrolyte in the lithium-ion battery is the amphiphilic quasi-solid polymer electrolyte according to claim 7.
Citation Information
Patent Citations
Solid polymer electrolyte and preparation method thereof
CN111430807A
High-safety solid-state electrolyte, preparation method and application thereof
CN111969245A